Membrane for rooftop extensions: an economical and environmentally efficient alternative - Macieira, Mónica Raquel Fernandes (2019)
Alternative solutions must be studied when the costs and weight of the constructive solution are inhibiting factors (for owners, designers, investors and different parties involved). The increasing importance given today to the environmental compatibility leads designers to combine both the use of energy efficient materials and technical solutions to maximize savings. Membrane building technologies are interesting alternatives in cases where the use of conventional/ traditional building options is limited, especially for its weight. This research intends to evaluate in what measure the membrane solutions can constitute an economical and environmental alternative to conventional rooftops extensions solutions, presenting a new outcome for the state of the art of lightweight design/ building applications field. For this, an old building from the 19th century, located in Porto (Portugal) was selected as case study and different solutions were applied to.